Analisis Keterlambatan Laporan Pertanggungjawaban Realisasi APBDes (Nagari): Studi Kasus pada Kabupaten Pasaman Barat - Nanda Rafsanjani; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2021)
This study aims to describe why the village goverment is late in submitting the village budget accountability report (APBDes) in West Pasaman Regency. This research is classified as a descriptive study. Sampling based on research objectives and data collection methods using interviews. This research was conducted in villages that were late in reporting the accountability for the realization of the (APBDes) in West Pasaman Regency. This study found that there are four obstacles that cause the village apparatus cannot make the report timely: quality of human resources, facilities & infrastructure, community participation, internal control. It suggested for further research to increase the sample and focus on comparing villages that are late and not late in reporting the budget realization accountability.